2007
DOI: 10.1165/rcmb.2007-0055oc
|View full text |Cite
|
Sign up to set email alerts
|

Steroid and Oxygen Effects on eIF4F Complex, mTOR, and ENaC Translation in Fetal Lung Epithelia

Abstract: Fetal distal lung epithelium (FDLE) must increase amiloride-sensitive epithelial Na(+) channel (ENaC) activity during the perinatal period to increase Na(+) transport and fluid clearance. Glucocorticosteroid (GC) levels increase, there is a 7-fold increase in Po(2) at birth, and we have previously shown that dexamethasone (DEX)-induced alpha-ENaC mRNA is efficiently translated only under postnatal (21%) O(2) (Otulakowski et al., AJRCMB 2006;34:204-212). Translation of mRNAs with long GC-rich 5'UTRs, such as al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 52 publications
2
23
0
Order By: Relevance
“…10,32 The effect of mTOR inhibition on cyst volume regression may be caused by increased apoptosis and/or by a potential effect on fluid reabsorption as suggested for fetal lung epithelia. 30,33 Nonetheless, our results support the concept of cyst regression by mTOR inhibitors when used at high enough concentrations.…”
Section: Discussionsupporting
confidence: 80%
“…10,32 The effect of mTOR inhibition on cyst volume regression may be caused by increased apoptosis and/or by a potential effect on fluid reabsorption as suggested for fetal lung epithelia. 30,33 Nonetheless, our results support the concept of cyst regression by mTOR inhibitors when used at high enough concentrations.…”
Section: Discussionsupporting
confidence: 80%
“…APC Min/ þ mice have an enhanced colonic Na þ absorption that even extends to the proximal colon . Interestingly, a previous report has shown that the expression of ENaC is regulated by a molecule downstream of mTOR, eukaryotic initiation factor (eIF4E) (Otulakowski et al, 2007); mTOR controls the phosphorylation of 4E-BP1, which inhibits eIF4E (Fingar et al, 2002;Koehl et al, 2005;Otulakowski et al, 2007). Remarkably, in our experiments, abnormal expressions of both b-and g-ENaC were reverted to the normal levels found in wt animals by rapamycin treatment (Figure 3a).…”
supporting
confidence: 63%
“…Finally, we examined the enhanced amiloride-sensitive Na þ absorption in the colon of APC Min/ þ animals, which is related to the possible upregulation of b-and g-subunits of ENaC. Interestingly, a previous study on fetal lung epithelia showed a pronounced increase in ENaC expression, which relied on the eukaryotic translation initiation factor eIF4E and activation of the mTOR pathway (Otulakowski et al, 2007). In this study, treatment with rapamycin led to a remarkable downregulation of ENaC expression and Na þ absorption by the colonic epithelium.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Both PO 2 and GC have been demonstrated to be important regulators of fetal lung maturation (16). We recently showed that a combination of fetal O 2 levels and DEX inhibited mTOR signaling in primary cultures of rat fetal distal lung epithelia (FDLE), yet this was not associated with increased expression of REDD1 in response to hypoxia and GC as would be predicted (17). Surprisingly, REDD1 was unresponsive to PO 2 and was repressed by 50 nM DEX.…”
mentioning
confidence: 92%